High-resolution annotation of the mouse preimplantation embryo transcriptome using long-read sequencing - Yunbo Qiao (Nature Portfolio, 2020)
Until now, the transcriptome of preimplantation mouse embryos has only been analysed by short-read sequencing. Here, the authors perform long-read sequencing to provide a more detailed transcriptome of the preimplantation mouse embryo, identifying various novel transcripts, for example Kdm4dl.